Greece : Ex-Post Evaluation of Exceptional Access Under the 2012 Extended Arrangement-Press Release; Staff Report;and Statement by the Executive Director for Greece. (IMF Staff Country Reports; Country Report, 2017)
This paper discusses Greece's Ex Post Evaluation of Exceptional Access Under the 2012 Extended Arrangement. Greece has made significant progress in unwinding its macroeconomic imbalances since the onset of its financial crisis. However, extensive fiscal consolidation and internal devaluation have come at a high cost to society, reflected in declining incomes and exceptionally high unemployment. On the basis of Greece's current policy adjustment program, long-term growth is expected to reach slightly lower than 1 percent, and the primary fiscal surplus is projected to come in at about 1.5 percent of GDP. Downside risks to the macroeconomic and fiscal outlook remain significant, related to incomplete or delayed policy implementation.